Aspectos clínico-epidemiológicos e tratamento da tripanosomose bovina por trypanosoma vivax no estado de Goiás - Bastos, Thiago Souza Azeredo (2019)
This study reports the first case of bovine trypanosomiasis caused by Trypanosoma vivax in Goiás, Brazil, as well as other cases that occurred within a period of 24 months, demonstrating epidemiological aspects such as needle sharing and commercialization of infected cows influencing the spread of this disease. Furthermore, it was observed that T. vivax was able to infect and develop the disease in calves when they were inoculated by the intradermal, subcutaneous, intramuscular or intravenous route. The presence of Anaplasma marginale latent in calves with trypanosomiasis interfer directly in the percentage of mortality of the animals. Finally, with regard to efficacy, only animals that received isometamidium were able to remain without new parasitaemia after 180 days of study. Treatment with diminazene allowed new parasitemia when reinfected 50 days after treatment and, finally, imidocarb was not effective in the treatment of bovine trypanosomosis. This is the first study that describes the presence of T. vivax, as well as its epidemiology in the State of Goiás, evaluated the infection capacity of this parasite by different pathways, clinical signs, and diagnostic methods and also evaluated the efficacy of the treatment with imidocarb, diminazene and isometamidium in cattle experimentally infected with T. vivax in Brazil.